dHealth 2020: biomedical informatics for health and care : proceedings of the 14th Health Informatics Meets Digital Health Conference - Schreier, Günter; Hayn, Dieter; Eggerth, Alphons (Studies in health technology and informatics, 2020)
Improved tracking of muscle tendon junctions in ultrasound images using speckle reduction -- Modeling external stimulation of excitable cells using a novel light-activated organic semiconductor technology -- Reusing data of an EU-wide EHR system for clinical trials: a capabilities analysis -- Encoding of numerical data for privacy-preserving record linkage -- Multivariable risk prediction of dysphagia in hospitalized patients using machine learning -- Identification and quantification of oxidized lipids in LC-MS lipidomics data -- Concept for visualisation of guideline adherence of medication prescriptions in a heart failure telehealth system -- Managing alternative patient appointments using p-graph methodology -- An evaluation of telemedicine systems in patient-centred care teams -- Learning analytics and the community of inquiry: indicators to analyze and visualize online-based learning -- Optimized patients' length of hospital stay with interventions based on health information technology: a review study -- Comparing monitoring results of two motion trackers for geriatric patients -- Surgical patients follow-up by smartphone-based applications: a systematic literature review -- Telemedical concepts for heart failure patients treated with a wearable cardioverter defibrillator -- Comparison of formative evaluation methods in the usability process on the example of a medical app -- Towards process mining in radiology: utilization of IHE SOLE -- FHIR analytics: pragmatic review of recent studies -- A supporting platform for comprehensive geriatric assessment and multi-modal tailored interventions -- Applying the FAIR data principles to the registry of vascular anomalies (VASCA) -- Children immunization app (CImA), low-cost digital solution for supporting Syrian refugees in Zaatari camp in Jordan: general description -- Evaluating performance and interpretability of machine learning methods for predicting delirium in gerontopsychiatric patients -- A systematic approach to quality requirement management in medical software -- A digital health coach for younger seniors: user centred requirements collection -- Nurses' viewpoints on barriers and facilitators to use hospital information systems -- 5058 the base frame of the algerian e-Health system: methodology to select the IHE integration profiles and the standards to control interoperability -- Effects of using hospital information systems on nurses' individual performance: a study on influential factors -- How to motivate children with severe disabilities to adhere to their therapy? -- The status quo of rare diseases centres for the development of a clinical decision support system -- A cross-sectional study -- Cerebral autoregulation monitoring and online Arden syntax clinical decision support for the treatment of intracranial hypertension in children with traumatic brain injury -- Exploring methods of implementing Arden Syntax for CDS hooks -- Assessing and improving the usability of the medical data models portal -- Medication apps: a systematic search and classification -- A computer model for patient individual parametrizing of ventricular tachycardia termination algorithms -- Stakeholder perspectives on the key components of a digital service platform supporting dementia: digiDEM Bayern -- The efficiency of different distance metrics for keyword-based search in medical documents: a short case study -- Implementing national electronic health records in nursing homes in Tyrol: a nursing management perspective -- Experimenting with generative adversarial networks to expand sparse physiological time-series data -- Mobile robotic telepresence between hospital and school: lessons learned -- Improving medical risk management using automotive standards -- Evaluation of different learning algorithms of neural networks for drug dosing recommendations in pediatrics.
Includes bibliographical references and indexes
Keywords: Electronic books; Congress